2022
DOI: 10.1002/eng2.12605
|View full text |Cite
|
Sign up to set email alerts
|

Synthesized heterogeneous nano‐catalyst from cow teeth for fatty acid methyl esters production through transesterification of waste vegetable frying oil and methanol: Characterization and optimization studies

Abstract: Using readily available biomass, it is possible to produce fatty acid methyl esters (FAME) at a low cost. This study focused on the transesterification process of waste frying vegetable oil to generate FAME (biodiesel) using a cost‐effective heterogeneous nano‐catalyst synthesized from waste cow teeth (CT). The cow teeth nano‐catalyst (CTNC) was synthesized via a three‐step method of calcination, hydration‐dehydration, and re‐calcination. The synthesized CTNC samples were characterized. The Box–Behnken design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 91 publications
0
1
0
Order By: Relevance
“…After three consecutive durability tests, the acetone conversion rate of the Ag–CeO 2 catalyst still exceeds 73%. Morphological distortion of nanocatalysts with special morphology is closely related to the doping concentration and technological conditions in the preparation process, such as quantitative doping of La 2 O 3 in the preparation of PVP/CS-La 2 O 3 nanoflowers, control of NO 3 – /CH 3 COO – in the precursor solution in the preparation of nanoparticles with excellent electrochemical performance, reaction time, and methanol content in the preparation of novel solid base CT-derived nanocatalysts . With the in-depth study of mullite nanocrystals by predecessors, it has been found that the size and morphology of nanomaterials play a crucial role in their physical and chemical properties. Especially, for the manganese-based mullite catalyst, the optimization of morphology will promote the increase of its specific surface area, surface unsaturated bonds, and active sites and thus substantially improve the activity of the catalyst …”
Section: Introductionmentioning
confidence: 99%
“…After three consecutive durability tests, the acetone conversion rate of the Ag–CeO 2 catalyst still exceeds 73%. Morphological distortion of nanocatalysts with special morphology is closely related to the doping concentration and technological conditions in the preparation process, such as quantitative doping of La 2 O 3 in the preparation of PVP/CS-La 2 O 3 nanoflowers, control of NO 3 – /CH 3 COO – in the precursor solution in the preparation of nanoparticles with excellent electrochemical performance, reaction time, and methanol content in the preparation of novel solid base CT-derived nanocatalysts . With the in-depth study of mullite nanocrystals by predecessors, it has been found that the size and morphology of nanomaterials play a crucial role in their physical and chemical properties. Especially, for the manganese-based mullite catalyst, the optimization of morphology will promote the increase of its specific surface area, surface unsaturated bonds, and active sites and thus substantially improve the activity of the catalyst …”
Section: Introductionmentioning
confidence: 99%